Intersection of Tradition and Well-Being: - Bilqis, Farikha; Vidyarini, Etika; Larasati, Mutiara Ayu; Ramadin, Tendy Yulisca; Saphiranti, Dona; Pasaribu, Yannes Martinus (Jurnal Desain Indonesia., 2024)
This study examines the intricate interrelationship between tradition, economic necessity, and physical health among women potters in Pagerjurang, Indonesia, who utilize a distinctive tilted pottery wheel technique. A mixed-methods approach, including ethnographic and the nordic body map questionnaire, was employed in order to investigate the impact of this traditional practice on the sitting posture and musculoskeletal issue of the potters. The study reveals that deeply entrenched social norms have shaped the evolution of pottery-making techniques, resulting in the design of perbot miring, a tilted pottery wheel that has become central to the Pagerjurang community's cultural identity and economic sustainability. Despite the reported physical discomfort, practice persists due to its cultural significance and economic importance. While initial observations suggested potential correlations between age, years of work, and physical complaints, statistical analysis showed weak, non-significant relationships. This research provides a foundation for future studies on ergonomic interventions that could preserve cultural practices while addressing physical health concerns in traditional pottery making in Pagerjurang.